Abnormal change in dynamic mechanical behavior of metallic glass by laser shock peening. (June 2021) - Li, Yansen; Wei, Yanpeng; Yi, Xu; Zhang, Kun; Wei, Bingchen
Highlights: The dynamic mechanical properties of MG before and after LSP were investigated. An abnormal increase of storage modulus near the Tg was observed after LSP. LSP induced a deviation between the dynamic mechanical result and theory prediction. The mechanism of structure evolution induced by LSP was discussed. Abstract: Laser shock peening (LSP) has been shown to be an effective technique to improve the plasticity of metallic glasses (MGs) by inducing residual stress and structural rejuvenation. However, the microstructural evolution and viscoelastic properties of MGs after LSP remain largely unknown. In this paper, the dynamic mechanical properties of Zr-based MG before and after LSP treatment were investigated. An abnormal increase of storage modulus near the glass transition temperature (Tg ) was observed after LSP. An increased deviation between the dynamic mechanical result and the quasi-point defect (QPD) theory prediction was also observed after the LSP treatment. A competing mechanism between the liquid-like region change and the pre-existing fringe-like precipitations is proposed to explain the unusual dynamic behaviors of MGs after LSP treatment. The results provide insightful information about the microstructural changes and viscoelastic properties of the MGs after LSP.